SymDiff: A language-agnostic semantic diff tool for imperative programs - Lahiri, Shuvendu; Hawblitzel, Chris; Kawaguchi, Ming; Rebelo, Henrique (Computer Aided Verification (CAV '12) (Tool description), 2012)
In this paper, we describe SymDiff, a language-agnostic tool for equivalence checking and displaying semantic (behavioral) differences over imperative programs. The tool operates at the level of an intermediate verification language Boogie, for which translations exist from various source languages such as C, C# and x86. We discuss the tool and the front-end interface to target various source languages. Finally, we provide a brief description of the front-end for C programs.